2017
DOI: 10.1007/s40266-017-0491-5
|View full text |Cite
|
Sign up to set email alerts
|

Post-transplant Viral Respiratory Infections in the Older Patient: Epidemiology, Diagnosis, and Management

Abstract: Organ and stem cell transplantation has been one of the greatest advances in modern medicine, and is the primary treatment modality for many end-stage diseases. As our population ages, so do the transplant recipients, and with that comes many new challenges. Respiratory viruses have been a large contributor to the mortality and morbidity of solid organ transplant (SOT) and hematopoietic stem cell transplant (HSCT) recipients. Respiratory viruses are generally a long-term complication of transplantation and pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 145 publications
(182 reference statements)
0
9
0
Order By: Relevance
“…Common respiratory viral infections (CRVIs) contribute to significant morbidity and mortality following hematopoietic stem cell transplantation (HSCT) [1][2][3][4]. T cell-mediated immune responses, including cytotoxic and helper T-lymphocyte activity, are the primary defense against viral infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common respiratory viral infections (CRVIs) contribute to significant morbidity and mortality following hematopoietic stem cell transplantation (HSCT) [1][2][3][4]. T cell-mediated immune responses, including cytotoxic and helper T-lymphocyte activity, are the primary defense against viral infections.…”
Section: Introductionmentioning
confidence: 99%
“…Factors contributing to the development and severity of a CRVI include type of HSCT (auto versus allo), the specific virus isolated, underlying hematologic malignancy, conditioning regimen, and the stem cell source for allo-HSCT recipients [2,[7][8][9][10]. The apparent increase in incidence of CRVI over the past 10 to 15 years could be attributed to widespread use of sensitive multiplex PCR to detect multiple viral (and bacterial) respiratory tract pathogens [3].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of 93 LTRs, 5/93 had respiratory viruses identified in bronchoalveolar lavage using viral culture and DFA staining, whereas 48/93 had respiratory viruses identified by NAT on the same samples [6]. Using multiplex NAT allows testing for several viruses simultaneously with a turnaround time of only 12-24 h [4]. Rapid antigen tests, allowing results within minutes, are clinically available for influenza and RSV only and suffer from low sensitivity [8].…”
Section: Diagnosismentioning
confidence: 99%
“…Parainfluenza virus (PIV) is a single-stranded RNA virus of the Paramyxoviridae family. There are four serotypes of PIV (1-4); serotype 3 is the most common and shows no seasonality and has been associated with outbreaks, whereas serotypes 1 and 2 appear in the fall and winter [4,71]. As with other respiratory viruses, PIV infection was mainly studied in LTRs, where it accounts for 3.6-20.9% of the respiratory viruses isolated [1,2,6].…”
Section: Parainfluenza Virusmentioning
confidence: 99%
See 1 more Smart Citation